Comunity and munipal plans for adaptation to climate change and resilience in Honduras - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
A set of 2 municipal plans and 6 community resilience plans has been built in 2021 by combining science outputs and local knowledge in Honduras.